Maintenance of totally implantable ports in Zhongshan Hospital: a best practice implementation project. (April 2016) - Shen, Yuehong; Zhang, Xin Ping; Ge, Feng; Huang, Hui; Li, Li
ABSTRACT: Background: The totally implantable port is a common central venous access device. The cost of implantation and maintenance however is very expensive. At present, the biggest problem regarding the promotion and the use of implantable ports in China is lack of well trained professional healthcare providers. Furthermore, maintenance of totally implantable ports by nurses is poor and patients may easily get complications. Aims/objectives: This project aimed to reduce the incidence of complications among general surgery patients with implantable ports, and improve healthcare safety and the care process, strictly in compliance with current evidence-based criteria. Methods: A baseline audit on maintenance of totally implantable ports utilizing the Joanna Briggs Institute Practical Application of Clinical Evidence System program was undertaken from 1 April to 15 May 2015 that involved 25 nurses and 25 patients. An intervention including education, demonstration, clinical practice and assessment was conducted from 16 May to 15 July 2015. A post-implementation re-audit was completed from 16 July to 10 August 2015. Results: The results of the audit for the nine audit criteria for totally implantable port maintenance were as follows: the compliance rate for Criteria 2 and 3 increased from 0% to 100%, Criterion 1 from 80% to 100%, Criterion 4 from 92% to 100%, Criterion 5 from 68% to 100%, Criterion 6 remained as 100%, Criterion 7 from 12% to 100%, Criterion 8 from 0% to 96% and Criterion 9 from 88% to 100%. During implementation we found four barriers and undertook measures to address them. Conclusions: This project achieved a significant improvement in establishing evidence-based practice regarding maintenance of totally implantable ports in the general surgery ward. Strategies in sustaining best practice should be developed in the future.